Factores sociodemográficos y nivel de autocuidado en pacientes adultos mayores con osteoartrosis del centro medico del centro Medico ESSALUD - Otuzco - Caffo González, Flor Elisa (2019)
The present investigation is a quantitative, descriptive, correlational approach. The purpose of this study was to determine the relationship between some sociodemographic factors and the level of self-care in patients with osteoarthritis at EsSalud-Otuzco Medical Center, in 2016. Self-care theory is supported by Orem. The sample consisted of 30 older adults with osteoarthroses who met the inclusion criteria; The data were collected through the test to assess sociodemographic factors and test to assess self-care. We took into account the bioethical principles, processing of data analysis was performed using the Statistics Independence Criteria test (Chi2). The results showed that more than 50% of older adults have a fluctuating age of 71 to 90 years (60.0%), are female (56.7%), have primary (43.3%) and secondary ( 23.3%) and most have a regular level of information on osteoarthritis (70%). Regarding self-care, more than 5% of the patients present a regular level (63.3%). It is concluded that there is a relationship with sex, education level and level of information p <0.05 and there is no relation with age (p> 0.05)